2014
DOI: 10.1186/1471-2091-15-19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of diosgenin in Dioscorea species and related medicinal plants by UPLC-DAD-MS

Abstract: BackgroundDioscorea is a genus of flowering plants, and some Dioscorea species are known and used as a source for the steroidal sapogenin diosgenin. To screen potential resource from Dioscorea species and related medicinal plants for diosgenin extraction, a rapid method to compare the contents of diosgenin in various plants is crucial.ResultsAn ultra-performance liquid chromatography (UPLC) coupled with diode array detection (DAD) and electrospray ionization mass spectrometry (ESI-MS) method was developed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 14 publications
0
40
0
4
Order By: Relevance
“…For example, an UPLC-DAD-MS was developed and validated for the identification and determination of diosgenin in several plants, and the presence of this steroid in three Dioscorea species and one species of Heterosmilax was demonstrated. In addition, it was also suggested that D. zingiberensis can be an important diosgenin source [117]. A UHPLC-based technique with evaporative light scattering detection (ELSD) was developed and validated for the determination of eleven steroidal saponins and diosgenin from several species of Dioscorea .…”
Section: Methodsmentioning
confidence: 99%
“…For example, an UPLC-DAD-MS was developed and validated for the identification and determination of diosgenin in several plants, and the presence of this steroid in three Dioscorea species and one species of Heterosmilax was demonstrated. In addition, it was also suggested that D. zingiberensis can be an important diosgenin source [117]. A UHPLC-based technique with evaporative light scattering detection (ELSD) was developed and validated for the determination of eleven steroidal saponins and diosgenin from several species of Dioscorea .…”
Section: Methodsmentioning
confidence: 99%
“…As diosgenin is the main aglycone of hydrolyzed DNTS, DPTS and DZTS (Tang et al, 2013;Yi et al, 2014b), and in particular, diosgenin have been reported for the anti-myocardial ischemia activity (Jayachandran et al, 2009), we hypothesize that diosgenin, as a metabolite, can be found due to oral administration of these three total saponins; this could constitute part of evidence supporting similarity in efficacy of these three herbs. (2) Are there significant differences in the metabolic profiles and metabolite levels of rat groups administered with saponins from these herbs?…”
Section: Introductionmentioning
confidence: 97%
“…4): Dioscin ( 1 ) [9, 13, 33–47], gracillin ( 2 ) [9, 13, 3336, 40, 42, 4548], trillin ( 3 ) [9, 14, 36, 42, 44, 45, 49, 50], diosgenin-3- O -[ α - l -rhamnopyranosyl-(1 → 3)- α - l -rhamnopyranosyl-(1 → 4)- α - l -rhamnopyranosyl-(1 → 4)]- β - d -glucopyranoside ( 4 ) [9, 25, 45], diosgenin-3- O -{ α - l -rhamnopyranosyl-(1 → 2)-[ α - l -rhamnopyranosyl-(1 → 3)]}- β - d -glucopyranoside ( 5 ) [25, 48, 51], diosgenin ( 6 ) [9, 36, 38, 42, 45–47, 49, 52], asperin ( 7 ) [9, 13, 45], 25-Δ-spirosta-3,5-diene ( 8 ) [9, 13, 14, 45–47, 53, 54], piscidic acid ( 9 ) [9, 13, 45–47, 55], 3 β ,26-glycol-25( R )-Δ5,20(22)-diene-furostanol-26- O - β - d -glucopyranoside ( 10 ) [40, 45, 56], progenin II ( 11 ) [9, 48, 52], prosapogenin A of dioscin ( 12 , progenin III) [9, 48], pseudo-protodioscin ( 13 ) [9, 39, 40], protodioscin ( 14 ) [9, 36, 39, 40, 42, 48, 52], protogracillin ( 15 ) [9, 36, 40, 42, 45, 48], kikuba-saponin ( 16 ) [9], smilagenone ( 17 ) [45], and epistephanine ( 18 ) [45, 46]. In addition, allantoin, sterols, flavones, resins, polysaccharides and starch have also been identified as constituents in the roots of D. nipp...…”
Section: Phytochemistrymentioning
confidence: 99%